Antidiabetic Activity Test of Ethyl Acetate Fraction of Takokak Fruit (Solanum torvum Swartz) Using Oral Glucose Tolerance Test (OGTT) Method - Rahmat Ismail; Ahlan Sangkal (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Takokak fruit is one of the plants that can be used to lower blood sugar levels. This study aims to identify the bioactive compounds of ethanol extract of takokak fruit and test the antidiabetic ethyl acetate fraction. Antidiabetic testing was carried out by in vivo testing using the Oral Glucose Tolerance Test (OGTT) method to see the decrease in blood glucose levels using white rats as test animals. The test results showed that takokak fruit contains flavonoids, steroids, and tannins. Fractionation is the process of extracting compounds from the extract using two types of solvents that do not mix with each other. The results of the antidiabetic test showed that the ethyl acetate fraction with glibenclamide as a comparator had the ability as an antidiabetic measured by the amount of difference in the decrease in blood glucose levels in the test animal group T₃₀ to T₁₂₀. From the results obtained, the average decrease in blood glucose levels in the negative control group (Na CMC) was 5.8 mg/dL, the positive control group (Glibenclamide) 21.03 mg/dL, and the fraction group 9.86 mg/dL. Takokak fruit has antidiabetic activity. Compounds that have antidiabetic activity are flavonoids, tannins, and steroids.